Safety systems design of VOC recovery process based on HAZOP and LOPA. Issue 4 (27th January 2014) - Lee, Sangick; Chang, Daejun
<x xml:space="preserve">Abstract</x> Crude tankers emit volatile organic compounds (VOCs) that are highly flammable and hazardous to human health and the environment. In light of these hazards, an international law has been enforced to regulate obligatory implementation of VOC management plans on board crude oil tankers. For the sake of safety, a risk assessment is performed to obtain information needed to make decisions about the safe design of a VOC recovery process. A hazard and operability analysis (HAZOP) is conducted to identify plausible hazardous scenarios. A layer of protection analysis (LOPA) is subsequently conducted to overcome the qualitative nature of HAZOP. A risk ranking method is used to select HAZOP results for use as inputs to LOPA for a more quantitative assessment. The initiating causes and existing protection layers are identified. The frequencies of the initiating causes and the probability of failure on demand (PFD) of each independent protection layers (IPL) are estimated quantitatively. The current mitigation is estimated by multiplying the initiating cause likelihoods by the PFDs for the applicable IPLs and adjustment values. The estimated current mitigation is then compared to a risk acceptance criterion to make recommendations for design improvements to further reduce risks to an acceptable level. © 2014 American Institute of Chemical Engineers Process Saf Prog 33: 339–344, 2014